1999
DOI: 10.2170/jjphysiol.49.457
|View full text |Cite
|
Sign up to set email alerts
|

Point-Mutations Related to the Loss of Batrachotoxin Binding Abolish the Grayanotoxin Effect in Na+ Channel Isoforms.

Abstract: The effect of grayanotoxin (GTX) on site-specific mutants of the alpha-subunit of rat skeletal muscle Na(+) channels (micro1) (micro1-I433K, micro1-N434K and micro1-L437K), which are resistant to batrachotoxin (BTX) (Wang and Wang (1998) Proc Natl Acad Sci USA, 95, 2653-2658) was studied using a whole-cell patch-clamp method. The GTX modification of the Na(+) channels was detected as a characteristic-sustained Na(+) current flow with repetitive pulses. We also studied the GTX action on mutants of the alpha-sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 0 publications
2
25
0
Order By: Relevance
“…The relative conductance was estimated to be 0.09 þ 0.02 (n = 4) for I433A, 0 (n = 2) for N434A and 0.33 þ 0.10 (n = 4) for L437A. An extensive reduction of sensitivity was recognized in I433A and N434A in accordance with the results previously obtained [3], but the relative conductance for L437 was as large (0.35) as for WT. As mentioned earlier, a similar change was recognized on switching the substituent from A to K in F1579 (see Table 1).…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…The relative conductance was estimated to be 0.09 þ 0.02 (n = 4) for I433A, 0 (n = 2) for N434A and 0.33 þ 0.10 (n = 4) for L437A. An extensive reduction of sensitivity was recognized in I433A and N434A in accordance with the results previously obtained [3], but the relative conductance for L437 was as large (0.35) as for WT. As mentioned earlier, a similar change was recognized on switching the substituent from A to K in F1579 (see Table 1).…”
Section: Discussionsupporting
confidence: 87%
“…A possible explanation is that BTX molecules fail to get access to the binding sites, which are located elsewhere, because of perturbation of the microenvironment around nearby binding sites. To con¢rm this supposition, we extended our study on the e¡ect of GTX I to three mutants made by alanine substitution, I433, N434 and L437, which were thought to be the binding sites using lysine substitution [3]. The relative conductance was estimated to be 0.09 þ 0.02 (n = 4) for I433A, 0 (n = 2) for N434A and 0.33 þ 0.10 (n = 4) for L437A.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The remainder of the pore is formed by each S6 segment of the four domains in close apposition to one another (13,14). Recent site-directed mutagenesis studies show that specific amino acid residues within each of the four S6 segments are important determinants of action of Site 2 toxins (15)(16)(17)(18)(19)(20)(21)(22)(23). Previously, we reported that D1S6 and D4S6 segments (but not D2S6 and D3S6) are required for GTX binding to the sodium channel (19 -21).…”
mentioning
confidence: 99%